Visual Outcome after Intravitreal Bevacizumab Injection in Macular Edema Secondary to Central Retinal Vein Occlusion - Nasir Bhatti, Mazhar-ul-Hassan, Umair Qidwai, Aziz-ur-Rehman, Niamatullah Sial (Pakistan Journal of Ophthalmology, 2011)
Objective: To evaluate visual outcome after intra-vitreal Bevacizumab in macular edema secondary to central retinal vein occlusion. Materials and Methods: This prospective study was performed at Isra Postgraduate Institute of Ophthalmology, Al-Ibrahim Eye Hospital, Malir, Karachi. Patients with macular edema secondary to central retinal vein occlusion, ischemic and non-ischemic were selected from 1st February 2009 to 31st July 2009, by using non-probability purposive sampling technique. Informed written consent was taken from the patients. Best-corrected visual acuity was checked before giving the intra-vitreal Bevacizumab injection and after 1st, 4th and 12th week. Results: Out of 41 patients included in the study 32 patients (78 %) showed visual improvement of at least one line on Snellen visual acuity chart (P value of <0.05), while rest of the 9 patients (22 %) did not show visual improvement. Conclusion: Intra-vitreal Bevacizumab injection results in modest visual improvement in patients with macular edema due to central retinal vein occlusion.